Sosialisasi Penguatan dan Pengembangan Kabupaten/Kota Layak Anak di Kabupaten Pasaman Barat - Irwan Irwan; Enceria Damanik; Yenni Melia; Elvawati Elvawati; Latifah Izzatul Jannah; Gebi Cahyani Lubis (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2022)
Socialization of Child Friendly Regency/City Development (KLA) is one form of government program activities in fulfilling children's rights. The socialization was carried out in the West Pasaman Region, initiated by the Office of Women's Empowerment, Child Protection, Population Control and Family Planning (DP3AP2KB) of West Sumatra Province. This activity aims to socialize Child Friendly Schools as one of the prerequisites for achieving Child Friendly Districts. This socialization method uses interactive lectures and discussions with DPRD members as well as all high school and vocational school principals in West Pasaman Regency and related local government organizations. The presentation shows that the socialization participants are very enthusiastic in asking questions and actively conducting discussions. Participants were given explanations regarding 24 indicators, namely; KLA local regulations, institutionalized KLA, community involvement (business and media), birth certificates, child-friendly information, child participation, consultation institutions for parents or families, alternative supervision institutions, child-friendly infrastructure, health facilities, prevalence of nutrition, PMBA, child-friendly health facilities, drinking water and sanitation, non-smoking areas, PAUD-HI, normal 12 years old, SRA, PKA, victims of violence and exploitation, victims of pornography and emergency situations, persons with disabilities and children with disabilities, stigma. The conclusion of this paper is that to achieve KLA, commitment from various related parties is needed.